PERAN DAN RESPON INDONESIA DALAM PENYELESAIAN SENGKETA LAUT CHINA SELATAN YANG BERDAMPAK PADA KLAIM NATUNA - Hanif, Najwa Silmisya (Jurnal Res Justitia: Jurnal Ilmu Hukum, 2025)
The South China Sea is a vital strategic waterway in the Asia Pacific region, rich in economic and political significance. While Indonesia does not directly claim territories in the South China Sea, China’s Nine-Dash Line declaration poses a direct threat to Indonesia’s sovereignty over the Natuna Islands. This is due to China's expansive territorial claims, which encroach upon Indonesia's continental shelf and Exclusive Economic Zone and directly challenge Indonesia's maritime rights as defined by the UNCLOS 1982. The research aims to examine Indonesia's response to China's aggressive actions in the South China Sea and to provide a legal analysis of the invalidity of China's claim to the Natuna Islands.